Effect of Probiotic Milk Containing L. Casei Shirota on Immunoglobulin-G Levels Among Anemic Adolescent Girls - Sugianti, Elya; Adi, Annis Catur; Ekayanti, Ikeu; Mahmudiono, Trias; Fatmaningrum, Widati; Yusmiati, Siti Nur Husnul (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Probiotic play important role on immune systems. This study was to investigate effect of probiotic milk containing L. casei Shirota on immunoglobulin G levels among anemic adolescent girls. A total of 22 adolescent girls aged 13-18 years with anemia were included on this study. The subjects were separated into 2 groups i.e. a probiotic group and a control group by simple random sampling. During 4 weeks, a probiotic group received 1 tablet of 60 Fe elemental + 250 Âµg folate acid once a week and probiotic milk once daily. While a control group received 1 tablet of 60 Fe elemental + 250 Âµg folate acid once a week. Blood samples were collected at 0 and 4 weeks and assayed for immunoglobulin G levels by ELISA. Immunoglobulin G levels were not significantly increase after intervention. Compared with control group, probiotic milk administration in probiotic group did not significantly increased immunoglobulin G levels (p>0.05). The probiotic milk containing L. casei Shirota did not improve immunoglobulin G levels on anemic adolescent girls.  Keywords: Probiotic, Immunoglobulin G levels, Anemia, Adolescent girls